NIFTy: near-infrared fluorescence (NIRF) imaging to prevent postsurgical hypoparathyroidism (PoSH) after thyroid surgery—a phase II/III pragmatic, multicentre randomised controlled trial protocol in patients undergoing a total or completion thyroidectomy - Deborah D Stocken; Maureen Twiddy; Hisham Mehanna; Jonathan Wadsley; Neil Corrigan; Katie Gordon; Julie Croft; Neil Sharma; Anna Perry; Mark Strachan; Gemma Ainsworth; Elizabeth Glenister; et al. (BMJ Open)
Introduction Postsurgical hypoparathyroidism (PoSH) is an iatrogenic condition that occurs as a complication of several different procedures with thyroid surgery being the most common. PoSH has significant short- and long-term morbidities. The volume of thyroid surgery is increasing, and PoSH is therefore likely to increase. Some studies have shown promising results using near-infrared fluorescence (NIRF) imaging in reducing the risk of PoSH which has the potential to significantly reduce morbidity and costs associated with monitoring and treatment.Methods and analysis NIFTy is an unblinded, parallel group, multicentre, seamless phase II/III randomised controlled trial in patients undergoing total or completion thyroidectomy. The trial incorporates a process evaluation (IDEAL (Idea, Development, Exploration, Assessment and Long-term follow-up framework) 2a) to inform the trial protocol, a phase II (IDEAL 2b) analysis using a surrogate primary outcome of 1 day transient hypocalcaemia to determine early futility and phase III (IDEAL 3) assessment of the primary outcome of PoSH at 6 months after surgery. 454 participants will be randomised on a 1:1 basis to evaluate thyroid surgery with NIRF and indocyanine green against standard thyroid surgery in reducing PoSH at 6 months after surgery, with the phase II analysis occurring once data are available for 200 participants. Analysis in both phases will be using multilevel logistic regression incorporating random effects with respect to surgeon and adjusting for minimisation factors. Phase III secondary outcomes include protracted hypoparathyroidism, hypercalcaemia, complications, length of stay, readmissions and patient reported quality of life using the Short Form 36 Health Survey Questionnaire and Hypoparathyroid Patient Questionnaire instruments.Ethics and dissemination NIFTy is funded by National Institute for Health and Care Research Efficacy and Mechanism Evaluation Programme (Grant Ref: 17/11/27) and approved by a Research Ethics Committee (reference: 21/WA/0375) and Health Research Authority (HRA). Trial results will be disseminated through conference presentations, peer-reviewed publication and through relevant patient groups.Trial registration number ISRCTN59074092.